The Use of Methylphenidate to Improve Executive Functioning in Pediatric Traumatic Brain Injury: A Systematic Review and Meta-Analysis - Anna Pitt-Francis; Andrew R. Stevens; Zubair Ahmed; Valentina Di Pietro (Trauma Care)
Background/Objectives: This systematic review aimed to investigate the efficacy of methylphenidate medication in the treatment of cognitive problems, such as attention, following pediatric traumatic brain injury. Previous reviews have focused on a broader population of acquired brain injury in pediatrics. Methods: Six databases were systematically searched, and eleven relevant reports were included, of which five were randomised controlled trials (RCTs) and six were prospective cohort designs with no control arm. The risk of bias was assessed for each of the studies using appropriate tools. Results: Eleven studies were included in this study for data extraction consisting of 376 participants. Our primary outcome of the efficacy of methylphenidate in improving attention was assessed in the included studies using a variety of tools. A meta-analysis was only possible for studies using the continuous performance test data, which showed an overall insignificant reduction of 36.07 (95% CI [−96.94, 24.80], p = 0.25). Other outcomes, such as the Conners’ rating scale and the behaviour rating interview of executive function, also did not show an overall difference after methylphenidate treatment. However, the risk of bias across all studies was judged as moderate to high. Conclusions: We conclude that there is currently no evidence to support the use of methylphenidate to improve cognitive outcomes in pediatric traumatic brain injury patients. Significantly larger high-quality studies are needed to determine an effect on executive functioning outcomes after methylphenidate treatment in pediatric traumatic brain injury.